Climate change policy and burden sharing in the European Union - Schmidt, Tobias F. N.,Koschel, Henrike (ZEW, 1998)
The objective of this paper is to present different equity rules that can be applied to the initial allocation of greenhouse gas entitlements and to analyse the potential impacts of these rules EU-wide as well as on the level of member states. The methodological framework used in the empirical part of the paper is based on the GEM-E3 model, a multi-country and multi-sectoral computable general equilibrium model for fourteen EU-member states. The major finding of the paper is that being ex ante favoured with respect to the initial allocation of permits might not hold ex post, i.e. when trade of permits and actual emission reductions are carried out. The reason can be found in two effects. First, the interdependence of the EU economies allows smaller economies not to make full use of the advantages they get through the ability-to-pay allocation: The negative impact on the economic perfomance of the big economies leads to a drop of export demand in the smaller economies, which in turn lowers the expected positive impact on welfare in the latter ones. Second, the way of how a surplus of permits in a particular country is used has considerable impacts on consumer welfare. Selling the surplus of permits on the international market and use the receipts to reduce public deficit is one way, but it has no direct impact on demand. Other, more demand stimulating recycling strategies of the surplus (e.g. a lump-sum transfer to households) might be more promising if welfare losses are to be minimzed. Both effects may outweigh the positive effect realized ex ante in some countries due to a more 'fair' initial allocation of permits. The outcome emphasizes the importance of a consideration of full general equilibrium effects across countries.
Keywords: Arbeitspapier; Graue Literatur; Buch; Klimaschutz; Luftverschmutzung; Emissionshandel; Allokation; Gerechtigkeit; Wohlfahrtsanalyse; Makroökonometrie; Allgemeines Gleichgewicht; EU-Staaten